Effects of flipped instruction on the performance and attitude of high school students in mathematics - Remalyn Q. Casem (Lectito Journals, 2016)
This study aimed to determine the effects of flipped instruction on the performance and attitude of high school students in Mathematics. The study made use of the true experimental design, specifically the pretest-posttest control group design. There were two instruments used to gather data, the pretest-posttest which was subjected to validity and reliability tests and the Modified Fennema-Sherman Attitudes Scale. It was found out that the experimental and control groups were comparable in the pretest and posttest. Comparison on their gain scores revealed significant difference with performance of the experimental group higher than the control group. There was no significant difference on the level of attitude of the participants in the experimental group before and after the study in terms of confidence in learning mathematics, attitude toward success in mathematics, mathematics anxiety and perception of teacher's attitudes. A very weak positive relationship existed between performance and attitudes toward mathematics.